MEL scripting for Maya animators - Wilkins, Mark R. (Morgan Kaufmann series in computer graphics and geometric modeling., 2005)
Trying to learn Maya programming from the documentation can be daunting whether or not you are a programmer. The first edition of MEL Scripting for Maya Animators earned the reputation as the best introductory book on MEL, Mayas scripting language. Now fully revised and updated, the second edition also includes new features, such as a discussion of global procedures, new chapters on fixing programming bottlenecks, advanced user interface techniques, and optimizing character rigs. New chapters on utility nodes and Maya's Web Panel feature provide new ideas on how to use MEL in applications. This new edition has kept the popular style of the first edition that offered very clear explanations of programming concepts to those without programming experience. A generous collection of code examples and Maya scene files is included on the companion Web site. This is a book for animators, artists, game developers, visual effects developers, and technical directors who want to learn the fundamentals of Maya, how to automate tasks, personalize user interfaces, build custom tools, and solve problems with MEL. * Fully updated with several new chapters. * Profusely illustrated and includes a companion Web site with numerous code examples and scene files. * The authors bring their extensive experience in professional production studios to provide expert guidance.